Indian J Pharm Sci 2020
DOI: 10.36468/pharmaceutical-sciences.664
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Amyrin Modulates P38 MAPK and Jnk Pathway to Inhibit Cell Proliferation and Induce ROS-mediated Apoptosis in HeLa Cells

Abstract: Anburaj et al.: β-Amyrin induces ROS-mediated apoptosisIt is aimed to investigate the effect of β-amyrin on p38 mitogen-activated protein kinase and Jun N-terminal kinase pathways and apoptosis in HeLa cells. HeLa treated cells were divided into 6 groups, group I-HeLa untreated cells as control, group II-dimethyl sulfoxide serve as vehicle control, group III-cisplatin as standard drug, group IV-β-amyrin-treated HeLa cells, group V-cells were pretreated with 100 μm N-acetyl-L-cystein for 1 hour and then treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The most active was H. scheppigianum CH 2 Cl 2 extract, which effect was the strongest on HeLa cells ( IC 50 =148.1 μg/mL), followed by A549 and LS174 cells ( IC 50 =294.0 and 308.9 μg/mL). Cytotoxic effect of this extract could be at least partly explained by the presence of α ‐ and β ‐amyrins, which ability to inhibit HeLa and/or A549 cells growth was demonstrated previously (both compounds were active against HeLa cells IC 50 =29.4 and 42.7 μg/mL; α ‐amyrin also against A549 cells IC 50 =31.3 μg/mL) [38,39] . It has been also found that β ‐amyrin achieved this effect in HeLa cells by producing ROS and consequently activating the signaling pathways that led to apoptosis [39] …”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The most active was H. scheppigianum CH 2 Cl 2 extract, which effect was the strongest on HeLa cells ( IC 50 =148.1 μg/mL), followed by A549 and LS174 cells ( IC 50 =294.0 and 308.9 μg/mL). Cytotoxic effect of this extract could be at least partly explained by the presence of α ‐ and β ‐amyrins, which ability to inhibit HeLa and/or A549 cells growth was demonstrated previously (both compounds were active against HeLa cells IC 50 =29.4 and 42.7 μg/mL; α ‐amyrin also against A549 cells IC 50 =31.3 μg/mL) [38,39] . It has been also found that β ‐amyrin achieved this effect in HeLa cells by producing ROS and consequently activating the signaling pathways that led to apoptosis [39] …”
Section: Resultssupporting
confidence: 61%
“…Cytotoxic effect of this extract could be at least partly explained by the presence of αand β-amyrins, which ability to inhibit HeLa and/or A549 cells growth was demonstrated previously (both compounds were active against HeLa cells IC 50 = 29.4 and 42.7 μg/mL; αamyrin also against A549 cells IC 50 = 31.3 μg/mL). [38,39] It has been also found that β-amyrin achieved this effect in HeLa cells by producing ROS and consequently activating the signaling pathways that led to apoptosis. [39] MeOH extracts also showed the highest activity on HeLa cells (IC 50 = 152.3 -303.2 μg/mL), followed by LS174 cells (IC 50 = 512.9 -689.7 μg/mL) and A549 cells (IC 50 = 625.2 -869.6 μg/mL).…”
Section: [C]mentioning
confidence: 95%
See 1 more Smart Citation
“…β-amyrin was the most potent chemical identified from CN, according to the network. In a study of cytotoxicity in human cervical adenocarcinoma (HeLa) cell-line, βamyrin induced apoptosis via an increase in reactive oxygen species (ROS) (21). In a study by Maiyo and colleagues, when β-amyrin extracted from Prunus africana was tested on colorectal carcinoma (Caco-2) cell lines, a significant cytotoxic activity was observed with an IC 50 value of 81 μg/mL (22).…”
Section: Discussionmentioning
confidence: 99%